Intercropping of menthol mint (Mentha arvensis L.) and spearmint (Mentha spicata L.) with sugarcane (Saccharum officinarum L.) - Singh, S K Kothari, U B (Journal of Spices and Aromatic Crops, 2004)
Field experiments were conducted at Lucknow (Uttar Pradesh), to study the effect of two sugarcane (Saccharum officinarum) cultivars namely, Co-S 767 (early, profuse tillering) and Co-Lk 8001 (late, shy tillering) and two planting geometries namely, 90 cm interval regular rows and 75 cm (row-to-row distance within the pair) x 120 cm (distance between two pairs of rows) paired rows for maximizing productivity, land use efficiency and income benefits through raising of menthol mint (Mentha arvensis) or spearmint (Mentha spicata) as intercrops in main as well as rata on crop of sugarcane. As a sale crop, the two sugarcane cultivars were equally productive during the main crop cycle but during'the rata on crop cycle cv. Co-S 767 yielded 15.3% more cane than cv. Co-Lk 8001. Sugarcane cv. Co-S 767 in paired row planting showed no reduction in cane yield by mint intercropping compared to 16.2% to 28.1% reduction in regular row planting during both main and rata on crop cycles. Sugarcane cv.Co-Lk 8001, however, did not suffer yield reduction by mint intercropping, irrespective of methods of sugarcane planting and crop cycles. However, menthol mint and spearmint suffered yield reduction (52% to 75%) as intercrops compared to their respective sale crop yields. In general; mint oil yield reductions were more during the ratoon crop cycle and when the companion crop was cv. Co-S 767. Mint intercropping with sugarcane cv. Co-Lk 8001 significantly improved land use efficiency (23% to 35%), gross (29% to 46%) and net returns (90% to 137%) and benefit-cost ratio (44% to 63%). Interplanting spearmint with sugarcane cv. Co-Lk 8001 resulted in maximum profits.